Characterization of alkanes and α-olefins from the thermo-chemical conversion of animal fat - Weber, Bernd; Stadlbauer, Ernst; Eichenauer, Sabrina; Frank, Andreas; Steffens, Diedrich; Schlich, Elmar; Schilling, Gerhard (Journal of biobased materials and bioenergy, 2014)
Lipids are important raw materials for chemical industry, food industry and cosmetics. In the context of replacing fossil resources, lipids are gaining considerable attention as sustainable feedstock for fuels and value-added chemicals. This study focuses on the composition of products - obtained from the thermo-chemical conversion of animal fat in a moving bed of sodium carbonate at 430 °C in the presence of water. Their chemical nature is determined by Fourier transform infrared spectroscopy (FTIR), proton nuclear magnetic resonance spectroscopy (1H NMR), - carbon nuclear magnetic resonance spectroscopy (13C NMR), chromatography and mass spectroscopy. The primary components of the bio-crude are a homologous series of straight chain alkanes and alkenes composed mostly of terminal double bonds. Fractionated distillation of the bio-crude - yields a hydrocarbon-based biodiesel. Its characteristics comply with nearly all parameters of European diesel fuel standards. Thus, it can be used in internal combustion engines. The gasoline fraction exhibits a quality comparable to that of straight run fractions from fossil fuel processing. - Moreover, with 18 mg/g methyl heptadecyl ketone is the primary polar component of bio-crude.